Level of vital and laboratory values on arrival, and increased risk of 7-day mortality among adult patients in the emergency department: a population-based cohort study - Annmarie Touborg Lassen; Peter Bank Pedersen; Daniel Pilsgaard Henriksen; Mikkel Brabrand (BMJ Open)
Objectives The aim of the study was to provide evidence for, at which vital and laboratory values, increased risk of 7-day mortality in acute adult patients on arrival to an emergency department (ED).Design A population-based cohort study.Setting ED at Odense University Hospital, Denmark.Participants All patients ≥18 years with a first-time contact within the study period, 1 April 2012 to 31 March 2015.Primary and secondary outcome measures Primary outcome was 7-day all-cause mortality.Variables were first recorded vital and laboratory values included in risk stratification scores; respiratory frequency, blood pressure, heart rate, Glasgow Coma Scale, temperature, saturation, creatinine, PaO2, platelet count and bilirubin. The association between values and mortality was described using a restricted cubic spline. A predefined 7-day mortality of 2.5% was chosen as a relevant threshold.Results We included 40 423 patients, 52.5% women, median age 57 (IQR 38–74) years and 7-day mortality 2.8%. Seven-day mortality of 2.5% had thresholds of respiratory frequency <12 and >18/min, systolic blood pressure <112 and >192 mm Hg, heart rate <54 and >102 beats/min, temperature <36.0°C and >39.8°C, saturation <97%, Glasgow Coma Scale score <15, creatinine <41 and >98 µmol/L for PaO2 <9.9 and >12.3 kPa, platelet count <165 and >327×109/L and bilirubin >12 µmol/L.Conclusion Vital values on arrival, outside the normal ranges for the measures, are indicative of increased risk of short-term mortality, and most of the value thresholds are included in the lowest urgency level in triage and risk stratification scoring systems.